Unexpected scarcity of ANME archaea in hydrocarbon seeps within Monterey Bay - A. C. Semler; A. E. Dekas (Biogeosciences)
Marine hydrocarbon seeps typically harbor a relatively predictable microbiome, including anaerobic methanotrophic (ANME) archaea. Here, we sampled two cold seeps in Monterey Bay, CA – Clam Field and Extrovert Cliff – which have been known for decades but never characterized microbiologically. Many aspects of these seeps were typical of seeps worldwide, including elevated methane and sulfide concentrations, 13C-depleted dissolved inorganic carbon, and the presence of characteristic macrofauna. However, we observed atypical microbial communities: extremely few ANME sequences were detected in either 16S rRNA or mcrA gene surveys at Clam Field (< 0.1 % of total community reads), even after 6 months of incubation with methane in the laboratory, and only slightly more ANME sequences were recovered from Extrovert Cliff (< 0.3 % of total community reads). At Clam Field, a lack of ANME mcrA transcription, a lack of methane-dependent sulfate reduction, and a linear porewater methane profile were consistent with low or absent methanotrophy. Although the reason for the scarcity of ANME archaea is still unclear, we postulate that non-methane hydrocarbon release excludes anaerobic methanotrophs directly or indirectly (e.g., through competitive interactions with hydrocarbon-degrading bacteria). Our findings highlight the potential for hydrocarbon seeps without this critical biofilter and therefore greater methane emissions from sediments.